Structural boundary and deep contact relationship between the Yangtze and Cathaysia Blocks from crustal thickness gradients - Han, Rubing; Yang, Dinghui; Li, Qiusheng; Fu, Wei; Zhu, Gaohua; Zhang, Hongshuang; Chen, Hao; Cheng, Yongzhi (Frontiers in Earth Science, 2023)
The deep boundary and contact relationship between the Yangtze and Cathaysia Blocks (the major tectonic units of the Southern China Block), as well as the tectonic attributes of the Jiangnan Orogenic Belt, have remained unknown or controversial. Using data recorded by 128 portable broadband stations and 96 permanent stations, we obtained high-resolution images of crustal thickness and Poisson’s ratio in the study area. The influences of crustal anisotropy and inclined interface were eliminated by using the newly proposed receiver function H–κ–c stacking method. We then used a gradient analysis method to obtain crustal thickness gradients at the boundary of the Yangtze and Cathaysia Blocks for the first time. Our results reveal that the crustal thickness varies from > 38 km in the Qinling–Dabie Orogenic Belt to < 30 km east of the Tanlu Fault and Cathaysia Block. Areas with high Poisson’s ratios (> 0.27) are concentrated on the flanks of the deep fault zone and the continental margin of the study area; those with low Poisson’s ratios (< 0.23) are concentrated in the Jiangnan Orogenic Belt. Large crustal thickness gradients are found beneath the eastern part of the Jiujiang–Shitai buried fault (> 5 km/°). Combined with the velocity structure and discontinuity characteristics at different depths, these findings suggest that the Jiujiang–Shitai fault may constitute a deep tectonic boundary dividing the Yangtze and Cathaysia Blocks on the lithospheric scale. Moreover, our results support that the Cathaysia Block subducted northwest-ward toward the southeastern margin of the Yangtze Block in the Neoproterozoic, and that the Jiujiang–Shitai buried fault and Jiangshan–Shaoxing fault are the deep and shallow crustal contact boundaries of the two Blocks, respectively; that is, the Yangtze Block overlaps the Cathaysia Block.